MANAJEMEN KURIKULUM MERDEKA PADA PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH BERBASIS PESANTREN (AL-QALAM: JURNAL KEPENDIDIKAN, 2025)
Education is a vehicle for improving and developing the quality of human resources. One of the factors that influences educational problems is educators. In general, educators are those who are responsible for the development of students. The subjects in this research were teachers and students of Al-Fatah Banjarnegara Vocational School. The research results revealed three studies, namely: 1). The Independent Curriculum Management Concept for Islamic Religious Education in Islamic Boarding School-Based Schools, Al-Fatah Banjarnegara Vocational School focuses on managing a curriculum that is more flexible, inclusive, and based on the needs of students. 2). The implementation of the Independent Curriculum Management for Islamic Religious Education in the Al Fatah Banjarnegara Islamic Boarding School-based school has four processes, namely: Planning, implementation, assessment, and P5. 3). There are four supporting and inhibiting factors, namely: quality teachers, quality students, adequate infrastructure, and solid teamwork. Meanwhile, the inhibiting factor is the lack of training for teachers in understanding and implementing the independent curriculum effectively